South Africa's medical brain drain: Myths, facts and what (not) to do - Jon Mortensen (Danish Institute for International Studies (DIIS), 2008)
A global shortage of health professionals makes it relatively easy for doctors and nurses from poor countries to emigrate to rich countries. This has raised fears of a medical brain drain from poor to rich countries and has been the subject of much - impassioned - debate. This paper questions the underlying rational behind South Africa's current policies toward the medical brain drain. In doing so, it also challenges the dominating view on the medical brain drain: that out-migration of health workers from developing countries has damaging consequences and curbing that migration is pivotal in safeguarding developing countries' health systems. A view which is rooted in a perhaps intuitively convincing assumption that out-migration and low levels of health workers are tightly correlated - that outward migration causes low levels of health workers in South Africa and elsewhere. This paper will argue that this is specious assumption. Consequently, it will question the calls for restraints on the recruitment of health workers from poor countries. Although such calls may occur to be morally superior, they have been largely ineffective and may be counterproductive in increasing the number of health workers in developing countries. The paper will argue that there is a need for a paradigm shift in the perspective on migration of health workers. The current paradigm is built on questionable theoretical assumptions and hypothesis. It overestimates the effectiveness of its policy recommendations and systematically ignores important negative side-effects of these. Further, it completely ignores positive impacts from out-migration and focuses solely on the negative; its conclusions are, thus, not surprising. Instead a perspective is needed which factors in the positive effects from migration of health workers, such as remittances, diaspora linkages, and so-called brain gain effects - and which provides realistic policy recom-mendations without counterproductive side effects. The paper will show that such a perspective - or rather a handful of several mutually reinforcing perspectives - is indeed emerging. It will formulate a number of policy recommendations specifically targeted at South Africa's shortage of health workers and how migration can play a role in meeting this challenge.
Keywords: 330; Gesundheitswesen; Gesundheitsberufe; Auswanderung; Brain Drain; Gesundheitsversorgung; Wirkungsanalyse; Südafrika